1995
DOI: 10.1002/jor.1100130620
|View full text |Cite
|
Sign up to set email alerts
|

Torsional loads in the early postoperative period following total hip replacement

Abstract: Torques generated in one subject during the early postoperative period were measured with a telemeterized total hip component. The patient was examined during gait, stair ascent, rising from a chair, and single-limb stance. The torques were plotted against both the resultant joint contact force and the force component directed along the stem axis. During gait, the maximum torque was 35 Nm, recorded at a walking velocity of 1.7 m/sec. The peak torques during stair ascent and during rising from a seated position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…The timed up and go test is the only functional test in which the control group surpassed the prostheses groups at all followups. One explanation could be the extremely high axial and rotational loads on the hip generated by the action of standing from a sitting position [8,26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The timed up and go test is the only functional test in which the control group surpassed the prostheses groups at all followups. One explanation could be the extremely high axial and rotational loads on the hip generated by the action of standing from a sitting position [8,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The operated patients may have had more difficulties in rising quickly from the chair, making the 180°turn at fast speed, or sitting on the chair. Extremely high axial and rotational loads on the hip are generated by this action [8,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are obvious disadvantages to such a system. Subsequently, in vivo forces have been successfully measured in orthopedics in the hip using telemetry links (Graichen et al, 1999;Bergmann et al, 1988Bergmann et al, , 1993Bassey et al, 1997;Kotzar et al, 1991Kotzar et al, , 1995Brand et al, 1994;Graichen and Bergmann, 1991;Davy et al, 1988;Hodge et al, 1989), spine (Calisse et al, 1999;Wilke et al, 1999;Rohlmann et al, 1995) and femur (Lu et al, 1998). Lu et al, 1997) The first report of a telemetered hip prosthesis came from English and Kilvington, who reported hip forces of 2.7 times the body weight during the stance phase of level walking without support (English and Kilvington, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Tibial prostheses have been instrumented with force transducers to measure tibial forces in vitro (Kaufman et al, 1996); however, direct measurement of tibial forces in vivo has not been reported. Telemetry has been shown to be a safe and accurate means of obtaining force data from implanted transducers and has been used to measure in vivo forces in the hip, spine, and femur (Graichen et al, 1999;Bergmann et al, 1988Bergmann et al, , 1993Bassey et al, 1997;Kotzar et al, 1991Kotzar et al, , 1995Brand et al, 1994;Graichen and Bergmann, 1991;Davy et al, 1988;Hodge et al, 1989;Calisse et al, 1999;Wilke et al, 1999;Rohlmann et al, 1995;Lu et al, 1997Lu et al, , 1998Taylor et al, 1997Taylor et al, , 1998. Hip forces measured through telemetry have typically been lower than those predicted mathematically.…”
Section: Introductionmentioning
confidence: 96%
“…However, to date, many of the technologies that seek to exploit this bone-implant loadsharing phenomena have been considered too large in dimension or involve implantation of an associated power supply. Previous investigations have been successful in determining forces in the hip [7]- [9], spine [10]- [12], and femur [13], [14]. However, due to the relatively large size of the sensors and associated hardware (signal conditioning, modulation, etc.…”
mentioning
confidence: 99%